Moving performances : divas, iconicity, and remembering the modern stage - Scheper, Jeanne, 1967- (Rutgers University Press, 2016)
Offering innovative theorizations of performance, reception, and affect, Moving Performances introduces readers to four remarkable divas from the early twentieth century-Aida Overton Walker, Loïe Fuller, Libby Holman, and Josephine Baker-who worked as both cultural producers and critics, deftly subverting the tropes of exoticism, orientalism, and primitivism commonly used to dismiss women of color. Scheper rejects iconic depictions of these divas as frozen in a past moment, and vividly demonstrates how their performances continue to inspire ongoing movements.